Anal Cancer and Anal Cancer Screening Knowledge, Attitudes, and Perceived Risk Among Women Living With HIV. Issue 1 (January 2021) - Rodriguez, Serena A.; Higashi, Robin T.; Betts, Andrea C.; Ortiz, Cynthia; Tiro, Jasmin A.; Luque, Amneris E.; Barnes, Arti
Abstract : Objectives: The aims of the study were (1) to describe anal cancer knowledge, perceived risk, screening barriers, and acceptability of sample self-collection among women living with HIV (WLWH) at an integrated safety-net system and (2) to describe differences in demographic and psychosocial variables among a subsample of WLWH with a history of abnormal cervical cytology results versus those with normal results. Materials and Methods: We conducted telephone surveys with English- and Spanish-speaking WLWH ( N = 99) and used electronic health record data to extract insurance type, CD4 + cell count, RNA viral load, and cervical cytology results. We calculated descriptive statistics for participant demographics, HIV laboratory results, and psychosocial variables. Among the subsample of women who completed a recent cervical Pap, we used Fisher exact test to assess differences in demographic variables, CD4 + counts, RNA viral loads, knowledge, awareness, acceptability, and perceived risk by cervical cytology results. Results: Most participants (70%) reported knowing nothing about anal cancer; 28% correctly responded that HIV increases one's chance of getting anal cancer. Most (68%) never heard of an anal Pap test. Forty percent would get an anal Pap if they could self-collect the sample, whereas 59% were neutral or disagreed. The 2 most commonly cited barriers to obtaining an anal Pap were "I do not know enough about it" ( n = 15) and "It might hurt" ( n = 9). Conclusions: This study highlights a gap in knowledge and awareness among WLWH regarding their heightened risk for anal cancer. It indicates the need for health education and suggests an opportunity for a self-collection intervention.